To Study the Impact of It Training In Cashless Banking in Sukma District of Chhattisgarh - Kumar Narad, Anuj (International Journal of Computer Sciences and Engineering, 2025)
Sukma district comes in “Red corridor” as it is affected by Maoists and struggling to get basic facilities like Railway network and Banking,due to lack of schools infrastructure and qualified teachers. Citizens are not that qualified to match other dominant societies so state government has taken initiatives for the development of IT skills in youth and made them skilled to open CSC (common service center) and Banking Kiosks centers that made it possible for Sukma district to become the first cashless district in Chhattisgarh in 2016.